(untitled) (Research, Society and Development, 2021)
In order to differentiate groups of hypocalcemic (G1) and normocalcemic animals (G2) and infer the influence of subclinical hypocalcemia on metabolic profiles, this study determined calcium concentrations during the transitional period in 35 dairy goats healthy, pregnant, primiparous or multiparous, crossbreed or pure-bred dairy goats producing average 3 kg/day/goat. Therefore, blood samples were collected before (30, 20 and 10 days before parturition), on the day of delivery and after parturition (10, 20, 30, 40, 50 and 60 days postpartum). The variables measured were glucose, nonesterified fatty acids, β-hydroxybutyrate, cholesterol, triglycerides, amylase, total protein, albumin, urea, creatinine, aspartate aminotransferase, gamma glutamyl transferase, creatine kinase, total calcium, phosphorus, magnesium, chlorides, cortisol and insulin, as well as ionized calcium (Ca++), sodium and potassium. Goats were considered to have subclinical hypocalcemia if Ca++ ≤0.72 mmol/L. The data were analyzed by ANOVA. In subclinically hypocalcemic goats, serum concentrations of Ca++ decreased earlier (10dbp) than in normocalcemic goats (parturition) and remained lower throughout the transitional period (p=0,004). Among the measured variables, Ca++ showed greater influence on the NEFA, glucose, insulin and total calcium but also influenced the protein profile. Lower food intake by goats with subclinical hypocalcemia was one of the main factors interfering with the metabolic profile and likely the productivity of these animals. Studies should be conducted to measure the effects of subclinical disease on the production rates and on the emergence of other transitional period diseases.